Mantle and crustal gases of the Colorado Plateau: Geochemistry, sources, and migration pathways. (15th September 2017) - Craddock, William H.; Blondes, Madalyn S.; DeVera, Christina A.; Hunt, Andrew G.
Abstract: The Colorado Plateau hosts several large accumulations of naturally occurring, non-hydrocarbon gases, including CO2, N2, and the noble gases, making it a good field location to study the fluxes of these gases within the crust and to the atmosphere. In this study, we present a compilation of 1252 published gas-composition measurements. The data reveal at least three natural gas associations in the field area, which are dominated by hydrocarbons, CO2, and N2  + He + Ar, respectively. Most gas accumulations of the region exhibit compositions that are intermediate between the three end members. The first non-hydrocarbon gas association is characterized by very high-purity CO2, in excess of 75 mol% (hereafter, %). Many of these high-purity CO2 fields have recently been well described and interpreted as magmatic in origin. The second non-hydrocarbon gas association is less well described on the Colorado Plateau. It exhibits He concentrations on the order of 1–10%, and centered log ratio biplots show that He occurs proportionally to both N2 and Ar. Overall ratios of N2 to He to Ar are ≈100:10:1 and correlation in concentrations of these gases suggests that they have been sourced from the same reservoir and/or by a common process. To complement the analysis of the gas-composition data, stable isotope and noble-gas isotope measurements are compiled or newly reported from 11 representative fields (previously published data from 4 fields and new data from 7 fields). Gas sampled from the Harley Dome gas field in Utah contains nearly pure N2  + He + Ar. The various compositional and stable and noble gas isotopic data for this gas indicate that noble gas molecule/isotope ratios are near crustal radiogenic production values and also suggest a crustal N2 source. Across the field area, most of the high-purity N2  + He + Ar gas accumulations are associated with the mapped surface trace of structures or sutures in the Precambrian basement and are often accumulated in lower parts of the overlying Phanerozoic sedimentary cover. The high-purity gas association mostly occurs in areas interior to the plateau that are characterized by a narrow range of elevated, moderate heat flow values (53–74 mW/m 2 ) in the ancient (1.8–1.6 Ga) basement terranes of the region. Collectively, the geochemical and geological data suggest that (1) the N2  + He + Ar gas association is sourced from a crustal reservoir, (2) the gas association migrates preferentially along structures in the Precambrian basement, and (3) the sourcing process relates to heating of the crust. Prospecting for noble-gas accumulations may target areas with elevated Cenozoic heat flow, ancient crust, and deep crustal structures that focus gas migration. High-purity CO2 gas may also migrate through regional basement structures, however, there is not always a clear spatial association. Rather, CO2 accumulations are more clearly associated with zones of high heat flow (>63 mW/m 2 ) that sit above hot upper mantle and are proximal to Cenozoic volcanic rocks near the plateau margins. These observations are consistent with previous interpretations of a magmatic gas source, which were based on geochemical measurements.